Shared Cared for Stable Glaucoma Patients: Economic Benefits and Patient-centered Outcomes of a Feasibility Trial. Issue 2 (February 2018) - Goh, David; de Korne, Dirk F.; Ho, Henrietta; Mathur, Ranjana; Chakraborty, Bibhas; Van Hai, Nguyen; Wai, Charity; Perera, Shamira; Aung, Tin; Wong, Tien Y.; Lamoureux, Ecosse L.
Abstract : Purpose: The purpose of this article is to assess the quality of care and economic benefits of a shared care model managing patients with stable glaucoma in a primary eye care (PEC) clinic compared with a tertiary specialist outpatient clinic (SOC) in Singapore. Patients and Methods: A randomized equivalence feasibility trial was preformed comparing the PEC with SOC models. Participants recruited from the SOC had no visual field progression or change in management for at least 3 years, were on a maximum of a single glaucoma medication, had no previous tube-shunt implant and were at least 3-year posttrabeculectomy surgery. Primary outcomes were clinical assessment and management, economic benefits, and patient satisfaction. Differences were analyzed using equivalence testing and generalized odds ratios. Results: The trial included 233 patients, consisting of 42.1% glaucoma disc suspects (PEC: 47.4%; SOC: 36.8%), 27.5% primary angle closure suspects (PEC: 25.0%; SOC: 29.9%), 13.7% with ocular hypertension (PEC: 13.8%; SOC: 13.7%), 3.9% with primary angle closure glaucoma (PEC: 4.3%; SOC: 3.4%), and 3.0% with primary open angle glaucoma (PEC: 1.7%; SOC: 4.3%). Glaucoma clinical care for patients at PEC was as good as SOC [rate difference, 6.83%; 95% confidence interval (CI), 2.84-11.12) and management (rate difference, 7.69%; 95% CI, 3.21-12.17). In 23 cases (9.9%), 5.2% at PEC and 14.5% at SOC, there was disconcordance with the gold standard of senior consultant. Patient satisfaction at the PEC was equally high when compared with SOC (generalized odds ratio, 1.43; CI, 0.50-2.00). Direct costs per patient visit were 43% lower at PEC compared with SOC. Conclusion: Managing stable glaucoma patients at a primary care setting is a cost saving, safe, and effective shared care while enhancing professional collaboration between hospital and community settings. Abstract : Supplemental Digital Content is available in the text.